2015
DOI: 10.1371/journal.pcbi.1004088
|View full text |Cite
|
Sign up to set email alerts
|

Mining Host-Pathogen Protein Interactions to Characterize Burkholderia mallei Infectivity Mechanisms

Abstract: Burkholderia pathogenicity relies on protein virulence factors to control and promote bacterial internalization, survival, and replication within eukaryotic host cells. We recently used yeast two-hybrid (Y2H) screening to identify a small set of novel Burkholderia proteins that were shown to attenuate disease progression in an aerosol infection animal model using the virulent Burkholderia mallei ATCC 23344 strain. Here, we performed an extended analysis of primarily nine B. mallei virulence factors and their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…1 ). Likewise, the shortest paths in combination with other centrality measures revealed novel genes, pathways, and microbial communities in other biological systems 44 , 45 , 65 67 . For instance, network topology analyses, i.e .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1 ). Likewise, the shortest paths in combination with other centrality measures revealed novel genes, pathways, and microbial communities in other biological systems 44 , 45 , 65 67 . For instance, network topology analyses, i.e .…”
Section: Discussionmentioning
confidence: 96%
“…shortest path on a large-scale dataset led to the discovery of a new signaling axes-related to Syk, a protein tyrosine kinase, which negatively affects tumor development and progression 66 . Similarly, network analysis in human- Burkholderia mallei recently showed that pathogen virulence factors interact with multifunctional host hub proteins to simultaneously manipulate a wide range of host cellular processes 65 . In another study, viral proteins also interact with key host proteins to hijack diverse signaling pathways for infectivity 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies demonstrated complete sterilizing immunity, several promising LAV and subunit vaccines against Burkholderia have been proposed. Most notably, a mutant strain deficient in iron transport and a type IV SS [Δ tonB/hcp1 ) [32]] and several mutant strains lacking functional virulence factor genes [39, 40] demonstrated significant protection against a lethal Burkholderia challenge. Although LAVs are potent stimulators of immunity, safety concerns make them unlikely candidates for clinical applications; therefore, subunit vaccines become more practical.…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1; [36, 23, 37]). Memisevic et al, used a bioinformatics and a yeast two-hybrid approach to identify uncharacterized and novel virulence factors that were conserved between both B. mallei and B. pseudomallei [38, 39]. Using this information, they created three B. mallei mutant strains (ΔBMAA0728, ΔBMAA1865, ΔBMAA0553), one of which (ΔBMAA0728) lacks the virulence gene encoding components of a type VI SS [38].…”
Section: Live-attenuated Vaccinesmentioning
confidence: 99%
“…, 4]. Host-pathogen protein interactions provide important insights into the molecular mechanisms of pathogenecity [5].…”
Section: Introductionmentioning
confidence: 99%